Acute Myeloid Leukaemia in Its Niche: the Bone Marrow Microenvironment in Acute Myeloid Leukaemia - Ladikou, E. E. (Curr Oncol Rep, 2020)
PURPOSE OF REVIEW: Acute myeloid leukaemia (AML) is a heterogeneous malignancy for which treatment options remain suboptimal. It is clear that a greater understanding of the biology of the AML niche will enable new therapeutic strategies to be developed in order to improve treatment outcomes for patients. RECENT FINDINGS: Recent evidence has highlighted the importance of the bone marrow microenvironment in protecting leukaemia cells, and in particular leukaemic stem cells from chemotherapy-induced cell death. This includes mesenchymal stem cells supporting growth and preventing apoptosis, and altered action and secretion profiles of other niche components including adipocytes, endothelial cells and T cells. SUMMARY: Here, we provide a detailed overview of the current understanding of the AML bone marrow microenvironment. Clinical trials of agents that mobilise leukaemic stem cells from the bone marrow are currently ongoing and show early promise. Future challenges will involve combining these novel therapies targeted at the AML niche with conventional chemotherapy treatment.